Teoria fuzzy intervalar aplicada no controle de um sistema de levitação magnética - Viganó, Ian da Silva (2021)
Magnetic levitation teory attracts a lot of interest from the academic community currently, as it has a great potential in present promising technologies to the market, mainly in the passenger and cargo transportation sector and in the industrial sector, providing a great positive impact for society and contributing to the your well-being. Under this premise this work proposes to analyze the application of a interval based fuzzy control as a better alternative for control design for systems of this class, analyzing the positive characteristics of the application of this control technique in the face of a traditional fuzzy aproach. The controllers were designed and tuned manually, in order to observe if the extra degree of freedom provided by the type-2 fuzzy technique presents a superior performance. The experimental results show that the type-2 fuzzy controller provides a superior performance to its type-1 counterpart in different aspects. With this methodology, the best characteristics of the different classes of control systems can be combined to achieve a more efficient and intelligent control scheme.